Synchrotron FTIR microspectroscopy revealed apoptosis-induced biomolecular changes of cholangiocarcinoma cells treated with ursolic acid - Maphanao, Pornpattra; Thanan, Raynoo; Loilome, Watcharin; Chio-Srichan, Sirinart; Wongwattanakul, Molin; Sakonsinsiri, Chadamas (Biochimica et biophysica acta. General subjects, 2020)
Ursolic acid (UA) is a natural triterpenoid which possesses anti-cancer activity. However, little is known regarding the activity and molecular mechanism of UA in cholangiocarcinoma (CCA). Thus, we investigated the effects of UA on growth inhibition and apoptosis induction through biomolecular changes in KKU-213 and KKU-055 CCA cell lines. The anti-proliferative effect of UA against CCA cells was evaluated using SRB assay. Changes in biomolecules were assessed by SR-FTIR microspectroscopy combined with PCA and conventional methods (i.e., Annexin V-FITC/PI staining for lipid alteration and apoptosis induction; Western blot analysis and caspase-3/7 activity assay for apoptotic protein detection). UA suppressed the proliferation of CCA cells in a dose- and time-dependent manner. SR-FTIR data revealed a significant alteration in lipids attributable to changes in apoptotic cell membranes, confirmed by Annexin V-FITC/PI staining. SR-FTIR data showed that UA promoted changes in the protein secondary structure. Elevated expression of Bax and decreased expression of Bcl-2 and survivin/BIRC5 along with augmented caspase-3/7 activity supported alterations in apoptosis-related proteins. SR-FTIR microspectroscopy was successfully used as a label-free technique to monitor apoptosis-induced biomolecular changes in UA-treated CCA cells. UA exerted the cytotoxic and apoptotic activities in CCA cells through alterations in membrane lipids and apoptotic proteins. UA could be a potential anti-CCA candidate and a chemical starting point for the discovery of novel anti-cancer agents. Our present study showed the first evidence that UA exhibited the anti-proliferative and pro-apoptotic activities toward CCA cells through changes in biomolecules, notably lipids and proteins. [Display omitted] •We show, for the first time, the anti-cholangiocarcinoma efficacy of ursolic acid.•SR-FTIR microspectroscopy shows evidence of lipid and protein alterations.•Ursolic acid affects lipid membranes, caspase-3/7 activity and apoptotic proteins.•Ursolic acid can be a potential candidate for treating cholangiocarcinoma.